2018
DOI: 10.1111/apm.12877
|View full text |Cite
|
Sign up to set email alerts
|

Hypochromatic large urothelial cells in urine cytology are indicative of high grade urothelial carcinoma

Abstract: In this study, we have examined 67 cytology specimens from patients from 2014 to 2016. The ratio man to women was 4:1 with a median age of 75 years (range: 55-87 years). Thin-Prep processed urinary cytology specimens demonstrated large urothelial cells, with cytologic features of malignancy, thus including hypochromatic nuclei with occasional peripherally accentuated chromatin rim. The cytological diagnosis of High Grade Urothelial Carcinoma (HGUC) was made in 55 patients while 12 specimens were classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
(18 reference statements)
2
24
0
Order By: Relevance
“…It has been reported that nuclei of HGUC cells may be even hypochromatic, and they may resemble umbrella cells and do not demonstrate an increased N/C ratio. [ 19 20 ] In their study with digital image analysis, McIntire et al . showed that N/C ratio cut-off values for SHGUC and HGUC were lower than 0.7 and they advocated reducing the N/C ratio below the current threshold suggested in TPS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nuclei of HGUC cells may be even hypochromatic, and they may resemble umbrella cells and do not demonstrate an increased N/C ratio. [ 19 20 ] In their study with digital image analysis, McIntire et al . showed that N/C ratio cut-off values for SHGUC and HGUC were lower than 0.7 and they advocated reducing the N/C ratio below the current threshold suggested in TPS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the performance and use of cytomorphological features for diagnosing HGUC. All four TPS criteria were reported to be crucial indicators in urine cytology diagnosis although the sensitivity, specificity, and risk of malignancy varied in different studies or clinical scenarios [12][13][14][15]. None of the four cytological features can be regarded as a single conclusive criterion for diagnosing HGUC.…”
Section: Discussionmentioning
confidence: 99%
“…Coarse chromatin alone was more specific than other individual features. [42631] Digital image analysis has been shown to support N/C ratio cutoff of 0.5 as a criterion for AUC. [32] A recently published study utilizing digital image analysis found that the average N/C ratio for HGUC was 0.57 and for SHGUC was 0.53, proposing reduction of the N/C ratio criterion to a cutoff below 0.7.…”
Section: Discussionmentioning
confidence: 99%